The use of game theory in regional economics: A quantitative retrospective - Silva, Sandra T.; Mota, Isabel; Grilo, Filipe (Papers in regional science, 2015)
One of the most powerful tools within social science in general and economics in particular is game theory. This methodology allows for the formal analysis of the interactions among economic agents and, therefore, it is particularly useful for the study of economic decisions regarding spatial issues. For this reason, a quantitative systematization of the use of this tool on regional economics research is a relevant topic in the agenda concerned with progress in regional science. In this paper we study research in regional economics and provide a quantitative retrospective of the use of game theory in this field. Our main goal is twofold. First, we intend to categorize the contributions in the use of this analytical tool – by main research subjects, by authors' affiliations, by journal, etc. – using a bibliometric approach. Second, by analysing co‐authoring and using social network analysis, we want to test the existence of structures of knowledge upon which distinct co‐authorship emerges. The results of this research provide a framework for analysing the potential use of game theory in regional economics, suggesting new future research directions. Resumen La teoría de juegos es una de las herramientas más poderosas de las ciencias sociales en general y de las ciencias económicas en particular. Esta metodología permite el análisis formal de las interacciones entre los agentes económicos y, por tanto, es útil en particular para el estudio de las decisiones económicas relativas a cuestiones espaciales. Por esta razón, la sistematización cuantitativa del uso de esta herramienta en la investigación económica regional es un tema relevante en la agenda que se ocupa del progreso de las ciencias regionales. En este artículo estudiamos la investigación en economía regional y ofrecemos una retrospectiva cuantitativa del uso de la teoría de juegos en este campo. Nuestro objetivo principal es doble. En primer lugar, queremos clasificar las contribuciones al uso de esta herramienta de análisis – en cuanto a los sujetos principales de la investigación, a las afiliaciones de los autores, por publicación académica, etc. – mediante un enfoque bibliométrico. En segundo lugar, por medio del análisis de co‐autoría y el análisis de redes sociales, queremos probar la existencia de estructuras de conocimiento a partir de las cuales emergen co‐autorías claras. Los resultados de esta investigación proporcionan un marco para el análisis del posible uso de la teoría de juegos en economía regional, lo que sugiere nuevas direcciones para futuras investigaciones.